2008
DOI: 10.2754/avb200877010065
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Ultrasonographic Monitoring of Folliculogenesis in Puerperal Ewes after Spring Lambing

Abstract: The time of the first ovulation depends on the sheep breed, feeding conditions, year season, length of lamb nursing and following galactopoiesis. The objective of the present study was to analyse the follicle status after parturition in non-lactating Improved Valachian ewes. Laparotomy with following ovariectomy was performed after lamb weaning (spring) on days 17, 24 and 32 after parturition. The ovaries were USG analysed with 5.0 MHz linear and 7.5 MHz convex transducer. Follicular data were analysed quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The ovary halves were processed using standard histological methods as described previously (24). Sections of ovarian tissues were stained with Mayer haematoxylin and eosin (25).…”
Section: Histological Analyses and Image Processingmentioning
confidence: 99%
“…The ovary halves were processed using standard histological methods as described previously (24). Sections of ovarian tissues were stained with Mayer haematoxylin and eosin (25).…”
Section: Histological Analyses and Image Processingmentioning
confidence: 99%
“…Bennett and Balvanera [23] support the claims by the authors of thios article about the occurrence of environmental burdens in the Spiš region as a consequence of particular former mining activities. The above-mentioned authors have elaborated on the monitoring report on the Spiš region area in which they documented the elevated values of heavy metals Zn and Cd in the environmental components in water and soil.…”
Section: Discussionmentioning
confidence: 58%
“…The analysed selected heavy metals were evaluated due to the increased occurrence of these metals in the concerned area, which have monitored in the past by the authors of the current article. The increased incidence of these heavy metals has been confirmed by the studies of several authors [1,23] who also monitored the target area. The concentrations of lead (Pb) and cadmium (Cd) in the experimental animals were determined using an inductively coupled plasma optical emission spectroscopy (ICP-OES) (PerkinElmer) OPTIMA 2100 DV.…”
Section: Methodsmentioning
confidence: 64%
“…Studies in ewes [6] indicated that residual local inhibition of follicular development by a CL of pregnancy extends to the postpartum period. Moreover, the number of small antral follicles (which constitute more than half of the total follicular population) was lowest on day 17 and highest on day 32, while the number of large follicles was highest on day 24 and slightly lower on day 32 postpartum [29]; it also seemed to be influenced by diet and can be increased by administration of GnRH [25]. In postpartum rats, suckling inhibits GnRH/LH-pulses, reduces follicular development and delays the resumption of ovulation [30].…”
Section: Discussionmentioning
confidence: 98%